Methamphetamine and inflammatory cytokines increase neuronal Na+/K+-ATPase isoform 3: relevance for HIV associated neurocognitive disorders. - Gurudutt Pendyala; James L Buescher; Howard S Fox (PLoS ONE, 2012)
Methamphetamine (METH) abuse in conjunction with human immunodeficiency virus (HIV) exacerbates neuropathogenesis and accelerates neurocognitive impairments in the central nervous system (CNS), collectively termed HIV Associated Neurocognitive Disorders (HAND). Since both HIV and METH have been implicated in altering the synaptic architecture, this study focused on investigating alterations in synaptic proteins. Employing a quantitative proteomics approach on synaptosomes isolated from the caudate nucleus from two groups of rhesus monkeys chronically infected with simian immunodeficiency virus (SIV) differing by one regimen, METH treatment, we identified the neuron specific Na(+)/K(+)-ATPase alpha 1 isoform 3 (ATP1A3) to be up regulated after METH treatment, and validated its up regulation by METH in vitro. Further studies on signaling mechanisms revealed that the activation of ATP1A3 involves the extracellular regulated kinase (ERK) pathway. Given its function in maintaining ionic gradients and emerging role as a signaling molecule, changes in ATP1A3 yields insights into the mechanisms associated with HAND and interactions with drugs of abuse.